2008
DOI: 10.1080/12265080802021177
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Dollarization: A Case Study for Cambodia, Laos, and Vietnam

Abstract: We model the dollarization of three transitional economies in south-east Asia: Cambodia, Laos, and Vietnam which have been experiencing the transition and reform process of the economy for the time period 1992-2007. Based on Rojas-Suarez (IMF Working Paper WP/92/33, 1992) work, we examine whether the holdings of US dollars depend on the effect of the expected rate of depreciation in market exchange rates as expected by the model. Also, we examine whether the effects are proportional to the degree of the dollar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 16 publications
2
15
0
Order By: Relevance
“…As the Laos Government did not impose any restrictions on FCD holdings in the domestic banking system during the period of study, the CS measured as the ratio of FCD to M2 can be applied and viewed as the lower bound of the level of CS in Laos. Previous studies using the ratio of FCD to M2 as a measure of CS for Laos include Chaleunsinh (); Toyoda and Kyophilavong (); Keovongvichith (); Menon (); Ra () and Kyophilavong ().…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…As the Laos Government did not impose any restrictions on FCD holdings in the domestic banking system during the period of study, the CS measured as the ratio of FCD to M2 can be applied and viewed as the lower bound of the level of CS in Laos. Previous studies using the ratio of FCD to M2 as a measure of CS for Laos include Chaleunsinh (); Toyoda and Kyophilavong (); Keovongvichith (); Menon (); Ra () and Kyophilavong ().…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because this study empirically investigates the determinants of CS using quarterly data for Laos over the period 1993–2012, it differs from two major studies that empirically investigate the causes of CS in Laos using time‐series analysis. These studies include de Zamarocksy and Sa () and Ra (). De Zamarocksy and Sa () conduct a causality test between inflation and CS, using monthly data from February 1995 to September 2001.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result was in line with that the depreciation of Jordanian dinar led to a decline in Jordanian dinar holding and increased US dollar holding by residents (Kasawneh et al, 2010). Moreover, Ra (2008) examined whether the holding of US dollar was due to the effect of the expected rate of depreciation in the exchange rate market of three transitional economies in South-East Asia: Cambodia, Laos, and Vietnam. He found that there was a positive effect of the expected rate of depreciation on the holding of US dollar in the above three countries.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its importance of this issue, only a few attempts have been made to evaluate dollarization especially in Cambodia. Among them, Kem (2001) shows a long-run relationship between the expected rate of depreciation and dollarization during the period 1993-2001, and Ra (2008 finds a positive effect of 5 Only non-poor people earn their income in the US dollar, whereas the rest (the poor) receive their income in the riel (Beresford et al, 2004;Kang, 2005). Moreover, the durable products with a high price are sold in the US dollar, and the prices of goods in the supermarkets and some shops are also labeled in the US dollar while the riel is used only for the change.…”
mentioning
confidence: 99%